2016
DOI: 10.1063/1.4953909
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of ammonium perchlorate: Raman spectroscopic constrains at high pressures and temperatures

Abstract: We present the pressure-temperature (PT) induced physical and chemical transformations in ammonium perchlorates (APs) up to 50 GPa and 450 °C, using diamond anvil cells and confocal micro-Raman spectroscopy, which provide new constraints for the phase diagram of AP. The results show spectral evidences for three new polymorphs (III, IV, and VI) of AP, in addition to two previously known phases (I and II), at various PT conditions with varying degrees of hydrogen bonding and lack of strong spectral evidence for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 25 publications
8
17
0
Order By: Relevance
“…As illustrated in Figure , the calculated total energy curves as a function of volume disclose that AP possesses the lowest energy structure when it crystallizes in the Pnma symmetry rather than Pna 2 1 crystal symmetry which is consistent with the experimental measurements. , However, there are minor differences in the molecular (NH 4 + and ClO 4 – ) arrangements between two space groups (see Figure ), resulting in much less energy difference (Δ E = ∼1 meV/f.u.) between these two structures which makes them practically indistinguishable .…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…As illustrated in Figure , the calculated total energy curves as a function of volume disclose that AP possesses the lowest energy structure when it crystallizes in the Pnma symmetry rather than Pna 2 1 crystal symmetry which is consistent with the experimental measurements. , However, there are minor differences in the molecular (NH 4 + and ClO 4 – ) arrangements between two space groups (see Figure ), resulting in much less energy difference (Δ E = ∼1 meV/f.u.) between these two structures which makes them practically indistinguishable .…”
Section: Resultssupporting
confidence: 82%
“…A high-pressure–temperature phase diagram of AP is determined using Raman spectroscopy up to 50 GPa and 450 °C, and they observed a series of phase transitions from phase I → II → III → IV at 4.5, 9.9, 27 and GPa, respectively . The latest combined high-pressure in situ and synchrotron ADXRD and Raman spectroscopic measurements determined that the high-pressure phase of AP crystallizes in P 2 1 2 1 2 1 and P 2 symmetries, respectively, and these observations are in contrast to the previously observed iso-structural transition in AP under high pressure. , From the theoretical perspective, Zhu et al reported thermophysical properties such as electronic, vibrational, and thermodynamics of AP and ammonium dinitramide (ADN) at ambient pressure. Further, they have extended their study to investigate the effect of hydrostatic pressure on structure, electronic, and vibrational properties of AP in Pna 2 1 crystal symmetry .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Compared with the stretching vibration peak of free water in Zn-MOF (3475 cm –1 ), the peak of Zn-MOF-NH 3 shows a shift to lower wavenumber (3419 cm –1 ), indicating the existence of strong hydrogen-bonding force between intercalated H 2 O and NH 4 + . The Raman spectrum (Figure S3b) of Zn-MOF–NH 3 shows new peaks at 1416 cm –1 , attributed to the asymmetric bending vibration of NH 4 + . , The TG curve (Figure S4) of NH 3 -derivative manifests relatively high guest molecule content. A 10.45% weight loss occurs at 30–185 °C, corresponding to the removal of four lattice water (theoretical value, 10.33%).…”
Section: Results and Discussionmentioning
confidence: 96%
“…+ . 31,32 The TG curve (Figure S4) of NH 3 -derivative manifests relatively high guest molecule content. A 10.45% weight loss occurs at 30−185 °C, corresponding to the removal of four lattice water (theoretical value, 10.33%).…”
Section: ■ Results and Discussionmentioning
confidence: 99%